Physicochemical characterization and in vitro biological evaluation of solid compounds from furazolidone-based cyclodextrins for use as leishmanicidal agents - Carvalho, Suzana Gonçalves [UNESP]; Cipriano, Daniel Fernandes; de Freitas, Jair Carlos Checon; Junior, Miguel Ângelo Schettino; Ocaris, Enrique Ronald Yapuchura; Teles, Carolina Bioni Garcia; de Jesus Gouveia, Aurileya; Rodrigues, Ricardo Pereira; Zanini, Marcos Santos; Villanova, Janaína Cecília Oliveira (Springer Nature, 2020)
The discovery of new drugs and dosage forms for the treatment of neglected tropical diseases, such as human and animal leishmaniasis, is gaining interest in the chemical, biological, pharmaceutical, and medical fields. Many pharmaceutical companies are exploring the use of old drugs to establishing new drug dosage forms and drug delivery systems, in particular for use in neglected diseases. The formation of complexes with cyclodextrins is widely used to improve the stability, solubility, and bioavailability of pharmaceutical drugs, as well as reduce both the toxicity and side effects of many of these drugs. The aim of this study was to characterize solid compounds obtained from the association between furazolidone (FZD) and β-cyclodextrin (β-CD) or hydroxypropyl-β-cyclodextrin (HP-β-CD). The solid compounds were prepared in molar ratios of 1:1 and 1:2 (drug:CD) by kneading and lyophilization. Molecular docking was used to predict the preferred relative orientation of FZD when bound in both studied cyclodextrins. The resulting solid compounds were qualitatively characterized by scanning electron microscopy (SEM), thermal analysis (DSC and TG/DTG), X-ray diffraction (XRD), Raman spectroscopy with image mapping (Raman mapping), and 13C nuclear magnetic resonance spectroscopy (13C NMR) in the solid state. The cytotoxicity of the compounds against THP-1 macrophages and the 50% growth inhibition (IC50) against Leishmania amazonensis promastigote forms were subsequently investigated using in vitro techniques. For all of the solid compounds obtained, the existence of an association between FZD and CD were confirmed by one or more characterization techniques (TG/DTG, DSC, SEM, XRD, RAMAN, and 13C NMR), particularly by a significant decrease in the crystallinity of these materials and a reduction in the melting enthalpy associated with furazolidone thermal events. The formation of more effective interactions occurred in the compounds prepared by lyophilization, in a 1:2 molar ratio of the two CDs studied. However, the formation of an inclusion complex was confirmed only for the solid compound obtained from HP-β-CD prepared by lyophilization (LHFZD1:2). The absence of cytotoxicity on the THP-1 macrophage lineages and the leishmanicidal activity were confirmed for all compounds. MHFZD1:2 and LHFZD1:2 were found to be very active against promastigote forms of L. amazonensis, while all others were considered only active. These results are in line with the literature, demonstrating the existence of biological activity for associations between drugs and CDs in the form of complexes and non-complexes. All solid compounds obtained were found to be promising for use as leishmanicidal agents against promastigote forms of L. amazonensis. [Figure not available: see fulltext.].
Keywords: 2-Hydroxypropyl-β-cyclodextrin; Inclusion complexes; Leishmanicidal activity; Non-complexes; β-Cyclodextrin